The effect of different exercise protocols on leptin levels and regional left ventricular diastolic heart function among professional swimmers - a comparison with untrained subjects: a Doppler tissue imaging study - Skalik, R.; Janocha, A.; Borodulin-Nadzieja, L.; Gozdzik, A.; Poreba, R.; Bialy, D.; Derkacz, A.; Obremska, M.; Calkosinski, I. (Medicina Sportiva, 2006)
Background: It is assumed that leptin affects the circulatory system. The aim of this study was to assess the influence of chronic, dynamic and static physical effort on leptin levels and regional diastolic heart function as measured by Tissue Doppler Echocardiography in endurance athletes and healthy volunteers. Material and Methods: A total of 120 persons participated in the study including 60 endurance athletes (professional swimmers) and 60 healthy volunteers with low physical activity. The blood concentration of leptin at rest was measured under fasting conditions in all the subjects. The leptin levels were also measured in 30 athletes and 30 volunteers immediately after dynamic and static exercises. Moreover, the echocardiographic interrogation of regional diastolic heart function was performed in 120 subjects at rest and in 60 subjects ( 30 athletes and 30 volunteers) shortly after dynamic and static physical effort. Results: The relationship between leptin levels and parameters of regional left ventricular function was not confirmed. A significant effect of acute and chronic physical effort on regional diastolic heart function was exhibited among professional swimmers. Conclusions:1. A significant relationship between regular physical training and leptin levels was not confirmed among professional swimmers, however acute dynamic exercise had a significant impact on blood concentrations of leptin, 2. leptin does not exert an immediate and significant effect on regional left ventricular heart function among professional swimmers, 3. the period of training significantly correlates with changes in regional diastolic heart function among athletes.